(untitled) (International Seven Journal of Multidisciplinary, 2024)
Dental implant surgery can be conducted through two main approaches: Traditional Surgery and Guided Surgery. This article offers a detailed comparison between these techniques, exploring their advantages, disadvantages, and clinical applications. Traditional Surgery, widely practiced, stands out for its intraoperative flexibility, allowing real-time adjustments, but it can be less precise and more invasive. In contrast, Guided Surgery, based on digital technology, offers greater precision and less invasiveness, although it involves higher costs and greater dependence on technological resources. The choice between the two techniques must consider factors such as the complexity of the case, the surgeon’s experience, and the patient’s expectations. The article concludes that both approaches have their role in clinical practice, and the decision on which one to use should be carefully tailored to the individual needs of each patient.